PENGUATAN WAWASAN KEBANGSAAN PADA GENERASI MUDA MELALUI INTERNALISASI NILAI-NILAI KEBERAGAMAAN - Sarah Daiyyah Istiqomah; Afiyatun Kholifah (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2025)
The lack of national insight of the younger generation amidst the rapid flow of globalization and development of information technology is a big challenge for the sustainability of the nation’s integrity. This research aims to analyze the strengthening of the nationalistic insight of the younger generation through the internalization of religious values. The method used is qualitative research based on library research with a descriptive-analytical approach. Data sources are taken from various scientific literatures related to national insight, young generation character, and religious values. The results show that national insight can be strengthened through the internalization of religious values such as tolerance, honesty, responsibility, and compassion. This internalization can be done through formal education, family, social environment, and digital media. The young generation has a strategic role as agents of change who are able to bridge national and religious values in the life of the nation.